2017
DOI: 10.1093/geront/gnx084
|View full text |Cite
|
Sign up to set email alerts
|

Keeping Things in Balance: Family Experiences of Living With Alzheimer’s Disease

Abstract: This study was novel in its design as it included the person with AD as part of the functioning family unit. The temporal stages and the key social processes identified have the potential to inform the development of "stage-specific" interventions for the support of the whole family at various points in time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 16 publications
1
19
0
3
Order By: Relevance
“…In addition, how families negotiated and agreed (or not) their roles and responsibilities in response to AD required considerable family work to maintain a balance (Esandi et al, 2018). In the present study, it is easy to see how families who had initially close relationships that remained close could “work together” (Keady & Nolan, 2003, p. 29), as could those whose relationship were initially more distant but become closer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, how families negotiated and agreed (or not) their roles and responsibilities in response to AD required considerable family work to maintain a balance (Esandi et al, 2018). In the present study, it is easy to see how families who had initially close relationships that remained close could “work together” (Keady & Nolan, 2003, p. 29), as could those whose relationship were initially more distant but become closer.…”
Section: Discussionmentioning
confidence: 99%
“…Within this context, families strive to balance the demands of providing the best care for their relative while maintaining the personal, social, and working life of the family (Quinn et al, 2015). But “keeping things in balance” (Esandi et al, 2018, p. e56) is no easy task and families often struggle to maintain a life outside of AD. The extent to which they are able to largely depends on families collectively agreeing how to redefine their roles and maintain supportive and cohesive family interactions and dynamics (Deist & Greeff, 2017; Esandi et al, 2018; Keady & Nolan, 2003; La Fontaine & Oyebode, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…El perfil sociodemográfico del cuidador más frecuente corresponde a una mujer, de 60 o más años, es decir, una edad en la que aparecen problemas de salud crónicos y un deterioro natural de la estructura física de la persona y que cuidan de sus parejas o de sus progenitores; que debe ejercer el rol de cuidadora de su familiar durante un período que en promedio durará un año antes del desenlace fatal de su familiar. Este perfil de cuidador sigue las mismascaracterísticas que los estudios consultados (19)(20)(21)(22). A mayor edad del cuidador mayor posibilidad de padecer afecciones físicas.…”
Section: Discussionunclassified
“…Given the importance of the CG's understanding of the PWD's care values for care planning, and the relatedness of incongruence to the dyad's relationship quality and individual well-being, the ability to characterize a more incongruent sub-group of family care dyads, and distinguish dyads that are at higher risk for belonging to it, would help focus efforts around improving dementia care planning in clinical settings. Several qualitative studies have identified typologies or archetypes in family care dyads, which helps organize and advance the science of dementia care both theoretically and clinically (Bangerter, Griffin, Zarit, & Havyer, 2017;Clemmensen, Busted, Soborg, & Bruun, 2016;Esandi, Nolan, Alfaro, & Canga-Armayor, 2017). The purpose of this study was to characterize distinct patterns (i.e.…”
mentioning
confidence: 99%